ANALISIS PENGARUH KEGUNAAN RING DIESEL PADA SALURAN BAHAN BAKAR SOLAR TERHADAP DAYA MESIN DIESEL - Budi Harjanto; Heri Wijanarko; Sukahar (JURNAL MEKANIKASISTA, 2025)
This study discusses the influence of an additional device installed on vehicles called the Diesel Ring. Based on existing facts, the performance of diesel engines today is still often questioned, especially in terms of power output. As we know, people currently demand greater power from diesel engines to achieve optimal results. This growing demand has led to the rise of many aftermarket devices on the market that claim to increase the power of diesel engines. Therefore, the Diesel Ring was selected as an alternative solution to address this issue, as it offers several advantages, such as the ability to enhance engine power. In addition, the diesel engine was chosen over the gasoline engine because diesel engines have several superior characteristics, including higher efficiency and longer engine lifespan. Based on the research results, it can be concluded that the installation of the Diesel Ring can improve the power output of a diesel engine, both at low and high engine speeds.